2022
DOI: 10.23910/2/2022.0427c
|View full text |Cite
|
Sign up to set email alerts
|

Management of Tomato Damping-off Disease in the Nursery Using of Trichoderma asperellum

Abstract: The study was conducted during 2018−19 and 2019−20 to evaluate effectiveness of the Trichoderma asperellum liquid formulation for the management of tomato damping-off in the nursery. The experiment was conducted for two consecutive seasons in a randomized block design with seven treatments and three replications. T. asperellum formulation improved seed germination and controlled the damping-off diseases in tomatoes when compared with control. All the treatments performed better over control, in the first seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…T. asperellum ZNW enhanced the vegetative growth of pea plants that were planted in infested or non-infested soil due to its ability to promote plant growth, antagonize G. ultimum NZW, and its ability to induce the defense-related enzymes, and improve the concentration of photosynthetic pigment. These improvements resemble those reported on the growth parameter of tomato due to T. asperellum , which is used as a bioagent against damping-off disease [ 73 ].…”
Section: Discussionsupporting
confidence: 77%
“…T. asperellum ZNW enhanced the vegetative growth of pea plants that were planted in infested or non-infested soil due to its ability to promote plant growth, antagonize G. ultimum NZW, and its ability to induce the defense-related enzymes, and improve the concentration of photosynthetic pigment. These improvements resemble those reported on the growth parameter of tomato due to T. asperellum , which is used as a bioagent against damping-off disease [ 73 ].…”
Section: Discussionsupporting
confidence: 77%
“…Before its application, appropriate moisture is required for its better multiplication. A study confirmed that Trichoderma-enriched compost used as a nursery bed amendment considerably enhanced the yield and growth of tomato seedlings [277]. Trichoderma-enriched compost also enhanced the soil fertility and increased the soil enzyme activity, indicating improved soil health.…”
Section: Nursery Bed Treatmentmentioning
confidence: 68%
“…Synthetic pesticides cause nearly two lakhs of deaths from poisoning each year, and 99% of them occur in developing countries (Arora et al, 2022). However, issues related to human and soil health, environmental hazards, and disturbed ecosystems pressurized the agriculturists to switch over towards the safer and eco-friendly plant protection approaches (Kumhar et al, 2022). One such technique is Soil solarisation which is an eco-friendly method adopted prior to planting where solar energy is used by covering soil with transparent plastic sheet to control soil borne plant pathogens (Kanaan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%